Facilities and Merdeka Curriculum Influence Students’ Achievement Through Knowledge and Learning Quality - Erni Ratna Dewi; Aminullah Alam (Universitas Negeri Makassar, 2022)
The study aims to identify the influence of facilities and the Merdeka Curriculum on students’ achievement through knowledge and learning quality. It is quantitative research with an ex post facto approach surveying 120 students selected through a purposive sampling technique. Data were analyzed using path analysis and the Sobel test. The findings show that facilities directly negatively and significantly influence the students’ achievement. Adequate learning facilities support the students’ learning quality. Learning quality has a positive and significant influence on students’ learning achievement. Facilities positively and significantly influence the Merdeka curriculum. It means that the presence of the Merdeka curriculum, which is being implemented, cannot be separated from the availability of facilities to support the learning activities at school